Symptomatic lateral ventricular cystic lesion in a young cat. Issue 1 (June 2020) - Debreuque, Maud; Ducerveau, Marie-Noelle; Valin, Isabelle; de Fornel, Pauline; Manassero, Mathieu; Thibaud, Jean-Laurent
Case summary: A 1.5-year-old male neutered Persian cat was referred for acute deterioration of chronic left head tilt and ataxia. A lateral intraventricular cystic lesion, closely associated with the left choroid plexus, was identified on MRI. The intralesional signal intensity and cytological analysis of the fluid revealed a liquid similar to cerebrospinal fluid. After trepanation, an endoscopic-assisted fenestration and aspiration of the cyst were performed to temporally relieve the high intracranial pressure while waiting for surgical cystoperitoneal shunt placement. Three weeks after surgery, clinical relapse and recurrence of the lesion were noted on the pre-cystoperitoneal shunting MRI. During anaesthesia, the cat arrested. Cardiac resuscitation was successfully performed and cystoperitoneal shunting was postponed. Global brain ischaemia was then suspected, based on major forebrain clinical signs and MRI abnormalities. During a 6-month recovery period, a further three fine-needle CT-guided aspirations of the lesion were required, owing to clinical recurrence and increased cyst size. Cystoperitoneal shunting was eventually performed, allowing persistent reduction of the lesion and long-term improvement of the cat's neurological status. Relevance and novel information: This is the first report of a symptomatic lateral intraventricular cystic lesion in a cat. A left lateral intraventricular choroid plexus cyst was suspected based on the MRI features. Our case suggests that endoscopic fenestration and CT-guided aspiration are not adequate treatments for long-term management. Cystoperitoneal shunting may be a safe procedure, allowing significant and stable reduction of the cystic lesion, associated with improvement in the cat's neurological status by preventing high intracranial pressure.